1995
DOI: 10.1063/1.360712
|View full text |Cite
|
Sign up to set email alerts
|

H, He, and N implant isolation of n-type GaN

Abstract: The effect of ion-implantation-induced damage on the resistivity of n-type GaN has been investigated. H, He, and N ions were studied. The resistivity as a function of temperature, implant concentration, and post-implant annealing temperature has been examined. Helium implantation produced material with an as-implanted resistivity of 1010 Ω-cm. He-implanted material remained highly resistive after an 800 °C furnace anneal. The damage associated with H implantation had a significant anneal stage at 250 °C and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
53
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(56 citation statements)
references
References 5 publications
2
53
0
1
Order By: Relevance
“…Each found that post-implantation annealing activates the dopants, but no estimates of the absolute PL efficiency were given. Recently, the electrical properties [8] [9] and thermal stability [10] [11] [12] of dopant-implanted GaN have received growing attention, highlighted by the demonstration of implant isolation for electronic devices [13] and the electrical activation of p-type Ca acceptors [14].…”
Section: Introductionmentioning
confidence: 99%
“…Each found that post-implantation annealing activates the dopants, but no estimates of the absolute PL efficiency were given. Recently, the electrical properties [8] [9] and thermal stability [10] [11] [12] of dopant-implanted GaN have received growing attention, highlighted by the demonstration of implant isolation for electronic devices [13] and the electrical activation of p-type Ca acceptors [14].…”
Section: Introductionmentioning
confidence: 99%
“…Implantation isolation have been studied in pure GaN or AlGaN material using H + , He + , N + , F + , Mg + , Ar + , and Zn + ions [2]- [8]. The O + ion implant isolation was also investigated on AlGaAs [9], InAlN [10], and GaN (n-type doping)/GaN materials [11] to study the isolation quality, and P/He, Ar + , and N + ions have been employed in AlGaN/GaN HEMTs [12]- [14].…”
mentioning
confidence: 99%
“…To date there has been a little work in the area of the device applications https://doi.org/10.1557/S1092578300003367 of ion implantation in GaN, and generally ion implantation has been used to introduce impurities in GaN for study of their optical properties as well as the damage and passivation processes in GaN [10]. Recently, both n-and p-type GaN, as well as semi-insulating (sheet resistance of annealing has been reported [12]. In addition, high-resistivity layers for increasing the Schottky barrier height were created by implantation Mg, Mg/P and Ca into n-GaN with subsequent activation annealing [13].…”
Section: Introductionmentioning
confidence: 99%